Chronic effects of exposure to polyethylene microplastics may be mitigated at the expense of growth and photosynthesis in reef-building corals - Rades, Marvin; Poschet, Gernot; Gegner, Hagen; Wilke, Thomas; Reichert, Jessica (Marine pollution bulletin, 2024)
The causes of the physiological effects of microplastic pollution, potentially harming reef-building corals, are unclear. Reasons might include increased energy demands for handling particles and immune reactions. This study is among the first assessing the effects of long-term microplastic exposure on coral physiology at realistic concentrations (200 polyethylene particles L−1). The coral species Acropora muricata, Pocillopora verrucosa, Porites lutea, and Heliopora coerulea were exposed to microplastics for 11 months, and energy reserves, metabolites, growth, and photosymbiont state were analyzed. Results showed an overall low impact on coral physiology, yet species-specific effects occurred. Specifically, H. coerulea exhibited reduced growth, P. lutea and A. muricata showed changes in photosynthetic efficiency, and A. muricata variations in taurine levels. These findings suggest that corals may possess compensatory mechanisms mitigating the effects of microplastics. However, realistic microplastic concentrations only occasionally affected corals. Yet, corals exposed to increasing pollution scenarios will likely experience more negative impacts.
Gesehen am 16.12.2024
Online verfügbar 24 June 2024, Version des Artikels 24 June 2024